LABOR MARKET IN CONDITIONS OF COVID-19 PANDEMIC EU VS. USA - Jolović, Nevena (Ekonomija - teorija i praksa, 2022)
Since March 2020, the global labor market has been exposed to exceptional shocks due to the outbreak of a global pandemic - Coronavirus Disease 2019 (COVID-19). The COVID-19 crisis has threatened subjects and shaken relations in labor markets around the world, and employment levels in the European Union (EU) and the United States of America (USA) have begun to oscillate significantly. The aim of the research is to review the trends observed in the labor markets of the EU and the USA during the first and second quarters of 2020, and to review the projections of eminent authors related to future trends in the mentioned markets. The analysis of the unemployment rate, as well as the policies and measures taken by the EU and USA governments in order to mitigate the consequences of the pandemic, were used in making the final assessment which of these systems suffered more damage, and which of them responded more adequately to crisis. The descriptive and comparative method, analysis and synthesis technique, as well as content analysis of available domestic and foreign literature, were used for research purposes. The result of the research is reflected in the observation that both the EU and the USA responded to the economic and social emergency, and through a number of initiatives supported employees and companies in their labor markets in a timely manner. Finally, the so-far analysis results show that after the first six months of 2020 the American labor market has been much more affected by the pandemic than the European labor market.